2021
DOI: 10.17230/ad-minister.38.5
|View full text |Cite
|
Sign up to set email alerts
|

Audit Fees and Audit Quality: Evidence from GCC Region

Abstract: This study examines the association of audit fees with audit quality among a total of 104 and 108 non-financial companies listed on GCC stock markets for the periods preceding and subsequent the event, respectively, over the period 2005–2010. Using OLS regression, the results show that there is a significantly positive association between audit fees and audit quality for the periods preceding and subsequent the new auditor selection. Further, the results of this study contribute to the existing theory and empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…As argued in previous research, higher fees are expected to reflect higher auditor effort. Several studies have shown that the correlation between audit fees and audit quality is significant and positive (Rahmina and Agoes, 2014;Tobi et al, 2016;Hakim and Mardijuwono, 2020;Aljaaidi et al, 2021), affirming that high audit fees are accompanied by an increase in audit quality. The higher the audit fee, the higher the audit quality.…”
Section: Literature Review Audit Fees and Audit Qualitymentioning
confidence: 99%
“…As argued in previous research, higher fees are expected to reflect higher auditor effort. Several studies have shown that the correlation between audit fees and audit quality is significant and positive (Rahmina and Agoes, 2014;Tobi et al, 2016;Hakim and Mardijuwono, 2020;Aljaaidi et al, 2021), affirming that high audit fees are accompanied by an increase in audit quality. The higher the audit fee, the higher the audit quality.…”
Section: Literature Review Audit Fees and Audit Qualitymentioning
confidence: 99%